Formulation and characterization of ketoprofen liquisolid compacts by Box-Behnken design - Vittal, G Vijayaranga; Deveswaran, R; Bharath, S; Basavaraj, BV; Madhavan, V (International Journal of Pharmaceutical Investigation)
Introduction: Liquisolid technique is used in delivery of lipophilic and poorly water soluble drugs through oral route. It involves dissolving water insoluble drugs in nonvolatile solvents and converting into acceptably flowing and compressible powders. The objective of the present work was to enhance the dissolution rate of ketoprofen using microcrystalline cellulose as carrier, aerosil 200 as coating material, and polyethylene glycol as nonvolatile water miscible liquid vehicle. Materials and Methods: The drug concentration was kept constant in all formulations at 40% w/w. Optimization was carried out using Box–Behnken design by selecting liquid load factor, amount of coating material, and amount of magnesium oxide as independent variables; cumulative percentage drug release and angle of repose were considered as dependent variables. Results: The Fourier transform infrared (FTIR) and differential scanning calorimetry (DSC) studies revealed that there was no possible interaction between drug and tablet excipients. Prepared ketoprofen liquisolid tablets were evaluated for hardness, weight variation, friability, in-vitro disintegration time, drug content uniformity, and invitro dissolution studies. The optimized formulation yielded the response values, which were very close to the predicted values. The accelerated stability studies conducted showed that liquisolid tablets were not affected by ageing and there were no appreciable changes in the drug content.
Keywords: Box-Behnken design; dissolution; ketoprofen; liquisolid compacts